Orientación motivacional, apoyo a la autonomía y necesidades psicológicas en balonmano playa - Morillo Baro, J. P.; Reigal Garrido, R. E.; Hernández-Mendo, A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2018)
The aim of this study was to examine the relationship between motivational orientation and perceived autonomy support with the satisfaction of basic psychological needs in beach handball players. 112 players between 17 and 32 years (M = 23.23, SD = 6.81) participated in the study. Task and Ego Orientation in Sport Questionnaire (TEOSQ), Sport Climate Questionnaire (SDT) for the climate to support autonomy and Psychological Need Satisfaction in Exercise Scale (PNSE) was used. The analysis performed showed significant relationships between the constructs studied, emphasizing support for autonomy as the best predictor of the three basic psychological needs. Nevertheless, by gender the groups showed different predictive models.